The Rational Apocalypse of the Latitudinarians in Restoration England - Jeongkyu Park (2018)
This thesis examines latitudinarians’ apocalyptic ideas during the Restoration period. These Anglicans have been considered by historians in terms of their role in promoting rational theology. However, there has been little analysis of the whole aspects of latitudinarian apocalyptic belief. This thesis surveys a variety of works to demonstrate a continuing tradition of apocalyptic worldview in their political and religious from the Restoration to the Revolution of 1688-1689. Chapter one summarises the English apocalyptic tradition that spanned the sixteenth century to early seventeenth century. English Protestants formed the key patterns of apocalyptic thought, and this apocalyptic tradition continuously influenced the Cambridge Platonists and many latitudinarian divines in the seventeenth century. Chapter two demonstrates that apocalyptic notions played an important part in latitudinarians’ anti-Catholic sentiment. Chapter three explains how these moderate Anglicans utilized apocalyptic ideas to justify the English Reformation and the Church of England. Chapter four explores the way in which the latitudinarians placed the debate of the royal supremacy within the apocalyptic context of the godly ruler. Lastly, chapter five focuses on how their expectations of the future fulfilment of divine apocalyptic promises led to the emphasis of moral reform. The fear of divine judgment and the hope of complete salvation motivated the latitudinarian clergy to promote the moral reformation. It also demonstrates that the latitudinarians’ proposal of moral reform implied their optimistic view of human nature, perfectibility of men, achieved through religious edification. In a broad sense, the examination of various aspects of latitudinarians’ religious thought shows the existence of the traditional apocalyptic framework in late seventeenth-century England.